Proposal for Energy Social Responsibility - Vishakha Agrawal; Dhyani Mehta (Journal of Social and Development Sciences, 2016)
The paper significantly works upon, how as per the newly implemented mandate under ‘The Companies Act, 2013’ organizations in India having turnover >100 cr &>200 cr (PAN India) or having net profit of at least 5 Crore have to spend 2 percent of their profit as part of CSR Corporate Social Responsibility to carry a philanthropic activity. As a social responsibility towards environment sustainability, India needs to change to renewable sources of energy which are non-polluting which will also support increasing demand for power and electricity. For economic as well as environmental rationales, this paper tries to recommend ESR (Energy Sustainability Responsibility) that can be accumulated through monetary support by all of the BSE (Bombay Stock Exchange) and NSE (National Stock Exchange) companies that in contrast can be accommodated on the research and development as well as infrastructural development of non-conventional and renewable sources of energy. The proposal can support India as well as countries across time zones to save fossil fuel reserves for future and create sustainability of these reserves. For the same objective the paper is addressing the applicability of ESR for setting up projects for renewable source of energy and cost involved in setting up of these projects vis-a-vis the efficient use of funds accumulated by the target companies by way of ESR: Energy Social Responsibility. The research design used is both descriptive and exploratory.